2023
DOI: 10.1039/d2ta08258f
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature electrochemically deposited polycrystalline SnO2 with adjustable work function for high-efficiency perovskite solar cells

Abstract: Last two years, the study of SnO2 preparation and optimization is proved to be an effective path toward the Schottky limit of perovskite solar cells. Here, we use an electrochemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Beyond the CBD method, Sun et al were the first to report on the electrochemical deposition (ECD) of polycrystalline SnO 2 at room temperature for large-area perovskite solar cells. 46 By controlling the pH of the electrolyte, this method allowed for the modification of the SnO 2 work function, facilitating a better energy alignment with the perovskite layer. At the optimal pH value of 1, the device surpassed the performance of those made with commercial colloidal dispersion SnO 2 , achieving a PCE of 19.21% in the active area of 0.99 cm 2 .…”
Section: Solution Processed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the CBD method, Sun et al were the first to report on the electrochemical deposition (ECD) of polycrystalline SnO 2 at room temperature for large-area perovskite solar cells. 46 By controlling the pH of the electrolyte, this method allowed for the modification of the SnO 2 work function, facilitating a better energy alignment with the perovskite layer. At the optimal pH value of 1, the device surpassed the performance of those made with commercial colloidal dispersion SnO 2 , achieving a PCE of 19.21% in the active area of 0.99 cm 2 .…”
Section: Solution Processed Methodsmentioning
confidence: 99%
“…(g) Image for electron chemical deposition (ECD). Reproduced with permission 46. Copyright 2023, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…Moreover, alterations in the energy level were noted, necessitating compatibility with diverse perovskite materials. [ 24 ] It is necessary to explore CBD‐SnO 2 film technology capable of achieving suitable perovskite without the need for annealing. To engender the deposition of polycrystalline SnO 2 via the CBD technique, one must adjust the electrolyte's pH through urea.…”
Section: Introductionmentioning
confidence: 99%
“…17 In contrast, SnO 2 with a wide band gap of 3.50 eV and a high electron mobility up to 250 cm 2 V À1 s À1 possess extremely high chemical and thermal stability. [18][19][20] SnO 2 nanoparticle based ETLs have been widely used in many types of photoelectric devices, including perovskite solar cells, [21][22][23] perovskite LEDs, 24 dye-sensitized solar cells, 25,26 thin-film transistors, [27][28][29] and organic solar cells. 30 It has been demonstrated that SnO 2 nanoparticle based ETLs are highly promising and general electron transport layer materials in various photoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…30 It has been demonstrated that SnO 2 nanoparticle based ETLs are highly promising and general electron transport layer materials in various photoelectric devices. [21][22][23][24][25][26][27][28][29][30] Nevertheless, bulk SnO 2 has a lower CBM position of À4.5 eV compared with the ZnO CBM position of À4.19 eV. 31 Normally, SnO 2 nanoparticles are not suitable as ETLs in cadmium-based QD-LEDs owing to their large electron injection barrier from SnO 2 to the QD emitter layer.…”
Section: Introductionmentioning
confidence: 99%